The Implementation of Clinical Supervision Models towards The Language Teaching and Learning - Herdiawan, Rama Dwika (Lembaga Penelitian Unswagati Cirebon Indonesia, 2018)
The effective supervision assists the teacher trainees or supervisee develop themselves in terms of the professional development such as teaching instrustions or methods, content, and also pedagogy. This article is aimed to explore as well as discuss the related literature particularly on clinical supervision. It describes best practices in clinical supervision through a set of relevant previous studies, and the roles of supervisor, supervisee, and the students in relation to the use of clinical supervision models used. It also deals with providing some useful guidelines for students and supervisors (not only for clinical students) to pursue the development of relationship among them in conducting the clinical supervision models. Therefore, the review of related literature focuses on clinical supervision which is expected to help the whole parties in the supervisory process to accelerate their goals as well as obejctives clearly, and also to minimize the potential problems and facilitate the implementation of effective supervision.Keywords: Clinical Supervision Models, , Teaching and Learning Language, Supervisor, Supervisee.